Pengembangan Bahan Ajar E-Book Interaktif Berbasis Flip Pdf Corporate Materi Gaya di Sekitar Kita IPAS Kelas IV MIN 1 Bojonegoro - Habibullah, Muhammad; Anjelina, Rita; Zakiyatur Rofi'ah, Firda (Universitas Nahdlatul Ulama Sunan Giri, 2024)
Abstract: IPAS learning in class IV MIN 1 Bojonegoro using printed books as teaching materials. The use of printed books show that there is not potential to utilise andimprove students’ learning experience. Learning in the classroom becomes less efeective, students feel bored and pay less attention during learning so that students are less active and do not understand the concept of IPAS. The solution to the problem is to develop interactive e-book teaching. The research objectives are 1) Knowing the procedure for developing interactive e-book teaching materials based on flip pdf corporate force material around us IPAS class IV MIN 1 Bojonegoro 2) Knowing the feasibility of developing interactive e-book teaching materials based on flip pdf corporate force material around us IPAS class IV MIN 1 Bojonegoro. This research uses the R&D (Research and Development) research method, and uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques used interviews, observation, documentation, questionnaires, and tests. The data analysis technique used validation analysis, student response questionnaire analysis and test result analysis. The results showed that interactive e-book is very feasible to use based on media design expert validation of 92%, material expert validation of 93% and linguist validation of 90%. Interactive e-books in the effective category based on the average pre-test score of 56,19 and post-test with an average of 86,67 which shows an increase in learning outcomes and the calculation of the n-gain score of 0,72 with a high category. The results of the student response questionnaire with a percentage of 85,10% with a very feasible category. Based on the results of the study, it can be concluded that the interactive e-book teaching materials based on flip pdf corporate force material around us IPAS is feasible and effective to use in learning.